Associations Between Body Mass Index, Body Image Satisfaction, and Self‐Weighing During a Behavioral Weight Loss Program - Armaan Shetty; Kathryn M. Ross (Obesity Science & Practice, 2025)
ABSTRACT Background Greater adherence to daily self‐weighing has been associated with improved outcomes within behavioral weight‐loss programs. Identifying factors that can predict adherence to self‐weighing may support the development of novel tailored interventions. Methods The current study examined whether baseline body mass index (BMI) and body image satisfaction (assessed via the Body Image States Scale [BISS]) predicted adherence to self‐weighing during a 16‐week behavioral weight‐loss program in 449 adults with obesity (mean ± SD age = 49.47 ± 11.37 years; BMI = 35.73 ± 4.03 kg/m2; 83.52% female, 74.16% White). Participants were provided with e‐scales and encouraged to self‐weigh daily during the program. Linear regressions were used to examine associations between BMI and BISS scores (and their interaction) and the proportion of program days that participants self‐weighed. Results At baseline, average (mean ± SD) BISS scores were 3.57 ± 1.28; higher BMI was associated with lower BISS scores, r = −0.11. Participants self‐weighed an average of 80.92 ± 23.35% of days during the intervention; greater self‐weighing was associated with greater weight loss, r = −0.56. Neither BMI nor BISS at baseline predicted self‐weighing adherence; moreover, there was not an interaction between BMI and BISS scores in relation to self‐weighing adherence. Conclusions Although results demonstrating negative associations between BMI and body image satisfaction and between self‐weighing adherence and weight loss were consistent with prior literature, the lack of an association between BMI, BISS, and self‐weighing was not consistent with hypotheses or the prior cross‐sectional literature. Given the role self‐weighing plays in behavioral weight‐loss programs, future research should aim to identify other predictors of self‐weighing adherence.